2020
DOI: 10.1142/s0218271820300049
|View full text |Cite
|
Sign up to set email alerts
|

Gravastar: An alternative to black hole

Abstract: In this work, we review thoroughly the origin, development and present status of gravastar which has been thought to be an alternative to black hole along with its future feasibility in the sense of astrophysical observation. The Mazur–Mottola model of the gravastar is introduced first followed by a review of its generalizations within the context of general relativity including physical applications like primordial and cylindrical gravastars. The study of gravastar in higher- and lower-dimensional general rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
2

Relationship

4
6

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 120 publications
0
16
0
Order By: Relevance
“…His work is then extended for f (R, T, R µν T µν ) [30] and f (R, G) [31] theories of gravity with spherical spacetimes. Recently, the origin as well as the existence of gravastars have been reviewed by Ray et al [32]. This paper extended the work of [33] and [34] for cylindrically symmetric metric in f (R, T ) theory.…”
Section: Introductionmentioning
confidence: 57%
“…His work is then extended for f (R, T, R µν T µν ) [30] and f (R, G) [31] theories of gravity with spherical spacetimes. Recently, the origin as well as the existence of gravastars have been reviewed by Ray et al [32]. This paper extended the work of [33] and [34] for cylindrically symmetric metric in f (R, T ) theory.…”
Section: Introductionmentioning
confidence: 57%
“…According to Cardoso et al [57,58], the ringdown signal of GW 150914 [56] has been detected by interferometric LIGO detectors are most probably generated by objects without event horizon which might be garvastar, though it yet to be confirmed [59] (in this context a detailed review on gravastar can be found in the ref. [60]).…”
Section: Boundary Conditionmentioning
confidence: 99%
“…Gravastars have also been explored in other modified gravity theories [78][79][80][81]. A comprehensive review on gravastar may be found in [82].…”
Section: Introductionmentioning
confidence: 99%